1981
DOI: 10.1111/j.1365-2044.1981.tb08867.x
|View full text |Cite
|
Sign up to set email alerts
|

High dose buprenorphine for postoperative analgesia

Abstract: S-nrYBuprenorphine was given intravenously to produce analgesia in the immediate postoperative period, the dose being titratedagainst the response of each patient in order to obtain complete freedom from pain. In SO patients following lower segment Caesarean section under general anaesthesia, buprenorphine in the dose range 0.4-7.0 mg was found to be a potent, long lasting and safe analgesic. Serial blood gas estimations performed on ten of the patients confkmed the clinically observed lack of respiratory depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 2 publications
2
31
1
Order By: Relevance
“…In contrast to the results from animal studies, a ceiling effect for analgesia has never been observed in humans [8,20,21]. On the other hand, studies in opioid-experienced but not dependent males showed a ceiling effect on subjective measures, such as positive mood and sedation, and respiratory depression at doses of sublingual buprenorphine up to 70-times the analgesic dose [21].…”
Section: Receptor Bindingmentioning
confidence: 71%
“…In contrast to the results from animal studies, a ceiling effect for analgesia has never been observed in humans [8,20,21]. On the other hand, studies in opioid-experienced but not dependent males showed a ceiling effect on subjective measures, such as positive mood and sedation, and respiratory depression at doses of sublingual buprenorphine up to 70-times the analgesic dose [21].…”
Section: Receptor Bindingmentioning
confidence: 71%
“…(Patel and Lindley, 2003). BUP has FDA approval as an analgesic (Budd, 1981;Christoph et al, 2005;Cowan et al, 1977;Jasinski et al, 1978;Kogel et al, 2005), however, multiple clinical trials of NK 1 antagonists as analgesics have failed (Goldstein et al, 1997(Goldstein et al, , 2001Hill, 2000). Specifically, APREP failed to demonstrate significant analgesic effects in phase-II clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The compound has a high affinity for opioid receptors, acting as a partial agonist at µ-opioid receptors and as an antagonist at κ-opioid receptors. Studies have shown sublingual and parenteral buprenorphine to be efficacious in the treatment of moderate to severe acute and chronic pain [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%